(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Diagnosis and treatment of acute otitis media, which develops in children against the background of diabetes mellitus, is one of the pressing problems of otorhinolaryngology and is the focus of attention of all specialists. Despite the achievements of world science, the treatment and prevention of this pathology in children remains one of the unresolved problems of modern medicine.